Is the correlation of the core muscle performance with shoulder pain and function altered by scapular dyskinesis in subjects with shoulder pain? - Oliveira, Felipe Augusto da Silva; Calixtre, Letícia Bojikian; Santos, Laís Regina de Holanda; Pitangui, Ana Carolina Rodarti; Araújo, Rodrigo Cappato de (Physiotherapy Practice & Research, 2024)
BACKGROUND: Daily activities that involve upper limb movements require muscle activation from different body parts by transferring forces and energy along the functional kinetic chain. The scapulae connect and transfer forces between the trunk and the upper limbs, so scapular dyskinesis may compromise the performance of the kinetic chain. OBJECTIVE: To assess the relationship between core muscle performance and shoulder pain and function in individuals with shoulder pain, with and without scapular dyskinesis. METHODS: Data was collected from 77 non-athlete adults aged between 18 and 50 years with shoulder pain, 45 had scapular dyskinesis. Core muscle performance was measured using the prone bridging test (PBT). Shoulder pain and disability were measured by the Shoulder Pain and Disability Index (SPADI), and the upper limbs' stability was assessed by the Closed Kinetic Chain Upper Extremity Stability Test (CKCUEST). The peak torque of shoulder external and internal rotators was measured using an isokinetic dynamometer. Multiple linear regression models evaluated the relationship between the PBT and CKCUEST, SPADI, and shoulder rotator strength. RESULTS: Significant correlations were found between the PBT and the SPADI total score (r = – 0.522), pain domain (r = – 0.513), and disability domain (r = – 0.501); normalized score (r = 0.593), and the power (r = 0.624) of the CKCUEST; and peak torque for external (r = 0.256) and internal (r = 0.292) rotations. Scapular dyskinesis did not influence the magnitude of the correlations and predictive values. CONCLUSION: The PBT was correlated with shoulder pain and function, but scapular dyskinesis did not affect the magnitude of these relationships.